Potential for Saving Drinking Water Through the Use of Rainwater in Social Housing in Viçosa-Brazil - Sánchez-Galvis, Juan Esteban (2024)
[Objective] The main objective of this research was to evaluate the potential for saving drinking water by using rainwater as a source of supply for non-potable purposes in two neighborhoods with social housing in the municipality of Viçosa, Minas Gerais, Brazil. [Methodology] The consumption statistics for each month of 2020 were used for each of the homes comprising the Benjamin José Cardoso and Sol Nascente Housing Complexes, and the fraction of drinking water that is destined in homes for non-potable purposes was estimated. The information corresponding to the monthly rainfall records of the last 50 years was analyzed and the monthly volume of rainwater that could be harvested in each house was calculated. [Results] The average monthly volume of rainwater that could be captured through the roof area of each dwelling is 3.39 m3. During the rainy months of the year, it would be feasible to save a higher percentage of water than that allocated for non-potable purposes. Sizing a rainwater reservoir that exceeds the monthly needs for non-potable purposes would allow the surplus of collected water to supply the liquid during the dry season. [Conclusions] Since the average percentage of savings in drinking water for both neighborhoods exceeded 53%, the saving of the monthly consumption can contribute to the reduction of payments for the drinking water service and the consumption of the liquid in the municipality, particularly during drought months.